A history of abuse - Samantha Weston (Oñati Socio-Legal Series)
The story of the past 30 years has been the relentless hollowing-out of industrial Britain, the single biggest change to the British economy in the post-war era. During this period, whole communities have become destabilised by mass long-term unemployment resulting in discarded generations that have been excluded socially and economically from the benefits widely available to those in work (Hutton, 1996; Buchanan, 2000). It has been against this backdrop that the youth of the 80s and 90s turned to heroin in an attempt to block out the harsh social and economic realities of their lives (Buchanan and Wyke, 1987). Drawing on semi-structured interviews with twelve opiate-involved users (OIUs), this paper illuminates the harms experienced by those who began their drug taking during the 80s and 90s. Particularly, I argue that the negative consequences brought about by the broad umbrella of drug treatment policy that adopts a framework of risk-based strategies designed to regulate and control drug users has had a cumulative effect contributing to further experiences of stigma, unemployment, physical and mental ill health.